1996
DOI: 10.1016/s1198-743x(14)65144-2
|View full text |Cite
|
Sign up to set email alerts
|

Disk diffusion, agar dilution and the E-test for susceptibility testing of Corynebacterium jeikeium

Abstract: OBJECTIVE: The susceptibilities to penicillin, tetracycline, erythromycin, gentamicin, vancomycin and teicoplanin of 58 strains of Corynebacterium jeikeium were assessed by disk diffusion and agar dilution reference methods. METHODS: Zone sizes and minimal inhibitory concentrations (MIC) by agar dilution were interpreted using the ranges in the NCCLS tables for organisms other than Haemophilus, Neisseria gonorrhoeae, and Streptococcus pneumoniae. RESULTS: By agar dilution, 14%, 88%, 17% and 26% of the 58 isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…Previous investigators noted that C. jeikeium isolates uniformly were susceptible to the glycopeptide antibiotics teicoplanin and vancomycin [6][7][8]49] and the experimental drug daptomycin [50]; our data were corroboratory. It should be stressed though that vancomycin was effective for chemotherapy of infection, but not for eradication of skin colonization [24].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Previous investigators noted that C. jeikeium isolates uniformly were susceptible to the glycopeptide antibiotics teicoplanin and vancomycin [6][7][8]49] and the experimental drug daptomycin [50]; our data were corroboratory. It should be stressed though that vancomycin was effective for chemotherapy of infection, but not for eradication of skin colonization [24].…”
Section: Discussionsupporting
confidence: 84%
“…With few exceptions, and like Pennekamp et al [49], we encountered very few discrepancies. The latter group of investigators proposed to adopt NCCLS interpretive criteria of penicillin G for Listeria monocytogenes as surrogate markers for C. jeikeium, i.e., a breakpoint of ^2 Ìg/ml; our data appear to indicate that the enterococcal breakpoint of ^8 Ìg/ml of penicillin G would perform just as well (table 2).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The E test values were always lower, down to 50% of the reference MIC values. Such discrepancies have been described by several authors for other antibiotics and aerobic as well as anaerobic isolates [26–28], both towards higher values [29–31] and lower values [32,33]. Basically, the E test is a diffusion method and it was originally described and patented by Professor Olof Vesterberg (Swedish Patent no.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the inhibition zone measurements can be processed in the local computer also offers other advantages. It has been reported that E test results sometimes deviate from the true MIC values [22–24], with values higher than the MIC [25–28] as well as lower than the MIC [29–32], sometimes depending on the combination of drug and species [33]. It has even been observed that E test deviations from the true MIC are greater at higher MIC values [28].…”
Section: Discussionmentioning
confidence: 99%